Molecular epidemiology of human immunodeficiency virus-infected individuals in Medellin, Colombia (2006)
ABSTRACT: To study the molecular epidemiology of human immunodeficiency virus type 1 (HIV-1) strains in Medellín, Colombia, 115 HIV-1-positive individuals who were recruited from an HIV outpatient hospital (Universitario San Vicente de Paul) during the period from July 2001 to January 2002 were genotyped. All samples were analyzed by envelope heteroduplex mobility assay and found to be subtype B. Twenty-four samples were randomly selected for sequencing of the protease and the reverse transcriptase regions; all isolates were found to be subtype B. Phylogenetic analysis of seven nearly full-length genomes showed that all samples were subtype B. This study shows that the HIV epidemic in Colombia continues to be dominated by the subtype B virus. The predominance of subtype B genotypes of HIV-1 strains in Medellín resembles what is seen in the nearby countries of Peru, Ecuador, and Venezuela.